ANALISIS PENGUASAAN "JINGGUO" DAN "TONGGUO" PADA MAHASISWA ANGKATAN 2019 PRODI PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Clarita, Stephanie; Veronica, Tjen; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
"Jingguo" and "Tongguo" have similar meanings, but the specific usage is different. ""Jingguo" means going through a certain period of time or space." ""Tongguo" means going from one end to the other, passing through a certain space non-stop, and does not mean going through a certain period of time." So many students cannot distinguish their usage. Therefore, the author chooses "Analysis Mastery of "Jingguo" and "Tongguo" by the 2019 Students Majoring in Chinese Language Education at Tanjungpura University" as the research topic. The purpose is to find out whether the students have mastered the usage of "Jingguo" and "Tongguo". This article uses literature research method and test research method. The test results show that the students"™ mastery of "Jingguo" and "Tongguo" are: the correct rate of "Jingguo" is 62.76%; the correct rate of "Tongguo" is 66.79%. this shows that the students"™ mastery of "Jingguo" and "Tongguo" is moderate. In addition, the most frequent problem among students is the misuse of "Jingguo". This happened because the students do not know much about the usage and the students do not understand the meaning of the question.